Algorithm for Detection of Hot Spots of Traffic Through Analysis of GPS Data - Tripathi, Jitesh Pati (My University, 2010)
Traffic congestion continues to be one of the major problems in various transportation systems. The ever increasing demand for mobility in urban centers has resulted in increased traffic congestion and a multitude of problems associated with it. People are especially concerned about those areas of the city which are regularly congested, because these areas could magnify the impact area and the duration of congestion. A prior knowledge about these areas and better understanding of impact of these areas could help into more appropriate traffic management strategies. This report present the method of detecting these areas ,which we call as ‘Hot-Spots’ in terms of road traffic and analyses the impact of these ‘Hot-Spots’ on traffic, both in terms of time and space. The Global Positioning System (GPS) data is used for this objective, as GPS has become a reliable, accurate and economically feasible positioning technology for probe vehicle. In the report, we present algorithms for the detection of the ‘Hot-Spots’, based on the speed of the probe vehicle and clustering (Fuzzy c-means algorithm) algorithm.
M.E. (CSED)
Keywords: Algorithms